The role of shoot-derived RNAs transported to plant root in response to abiotic stresses. (March 2023) - Liu, Zixi; Wang, Cuicui; Li, Xiaojun; Lu, Xiaohong; Liu, Mengshuang; Liu, Wenqian; Wang, Tao; Zhang, Xiaojing; Wang, Naonao; Gao, Lihong; Zhang, Wenna
Abstract: A large number of RNA molecules are transported over long-distance between shoots and roots via phloem in higher plants. Mobile RNA signals are important for plants to tackle abiotic stresses. Shoot-derived mobile RNAs can be involved in the response to different developmental or environmental signals in the root. Some environmental conditions such as climate change, water deficit, nutrient deficiency challenge modern agriculture with more expeditious abiotic stress conditions. Root architecture determines the ability of water and nutrient uptake and further abiotic stress tolerance, and shoot tissue also determines the balance between shoot-root relationship in plant growth and adaptations. Thus, it is necessary to understand the roles of shoot-derived RNA signals and their potential function in roots upon abiotic stresses in the model plants ( Arabidopsis thaliana and Nicotiana benthamiana ) and agricultural crops. In this review, we summarize the so-far discovered shoot-derived mobile RNA transportation to the root under abiotic stress conditions, e.g. drought, cold stress and nutrient deficiencies. Furthermore, we will focus on the biological relevance and the potential roles of these RNAs in root development and stress responses which will be an asset for the future breeding strategies. Highlights: Higher plants have developed numerous mechanisms that involve a precise shoot-root communication network. Long-distance RNA signals play a role in the communication between organs to tackle changing environment. Shoot-derived endogenous mobile RNAs were involved in the response to different developmental or environmental signals. The perspectives of the biological relevance and the potential central signaling pathway of these RNAs were proposed. Mobile modification-RNAs in root development and stress responses will be an asset for the future crop breeding strategies.